The effects of prosocial lyrics music on attentional bias. (January 2023) - Ma, Xie; Hu, Qijun; Xia, Liu; Zhang, Xinyue; Tao, Yun
Music is one of the most common social media in people's lives, and music with prosocial lyrics can promote an individual's prosocial behaviors. The social information processing model points out that an individual's behavior is affected by the selective processing of attentional information. This study used a spatial cue paradigm to compare the differences in attentional bias for prosocial cues between music with prosocial and neutral lyrics. The results show that music with prosocial lyrics can induce attentional engagement toward prosocial words, but not difficulty in attentional disengagement. This study revealed that individuals are more likely to pay attention to prosocial information after listening to music with prosocial lyrics, and that attention may play an important role in the impact of music on individuals' behaviors.